Seventeenth Century Science and the Arts - Toulmin, Stephen (Princeton Legacy Library, 2015)
Was there a continuity between the "vigorous art and the seminal science" of the seventeenth century? How did they affect one another? Which, if either, was dominant? Four distinguished scholars explore the relation between seventeenth century science and the creative arts in a series of four essays: Introduction, by Stephen E. Toulmin of Columbia; Science and Literature, by Douglas Bush of Harvard; Science and Visual Art, by James S. Ackerman of Harvard; and Scientific Empiricism in Musical Thought, by Claude V. Palisca of Yale.Originally published in 1961.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.